Jurnal Penyuluhan: Strategi Peningkatan Kinerja Penyuluh Pertanian dalam Pengembangan Agribisnis di Kabupaten Banyuwangi - Danang Sudarso , Widya Prakoso , Joyo Widakdo (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2014)
Agribusiness development in Banyuwangi growing supported by the agricultural extension. The role of agricultural extension is needed by communities and farmers. Therefore, strategies are needed to improve its performance, especially with the implementation of the difference between the central government and local governments (regional autonomy)